Hidden Hybridization and Habitat Differentiation in a Mediterranean Macrophyte, the Euryhaline Genus Ruppia - Beirinckx, Lise; Vanschoenwinkel, Bram; Triest, Ludwig (Frontiers in Plant Science, 2020)
In many aquatic plant taxa, classification and identification based on morphology has always been difficult. Molecular markers revealed that the complexity in several of these aquatic taxa could be addressed to recurrent hybridization events and cryptic species diversity. The submerged macrophyte genus Ruppia is one of these aquatic genera with a complex taxonomy due to the absence of clear distinguishable traits and several hybridization events. Two species co-exist throughout Europe, R. maritima and R. spiralis (previously known as R. cirrhosa), but recent molecular studies also found several indications of hybridization, introgression and chloroplast capture between these species. However, the full extent and frequency of hybridization and introgression in this genus has not been studied so far, nor is it clear how these hybrid lineages can co-exist locally with their parental species. In this paper, we wanted to detect whether a single coastal wetland where both species co-exist can act as a Ruppia hybrid zone. As a case study, we chose the Camargue, a Mediterranean coastal wetland that harbours a wide diversity in aquatic habitats, especially in terms of salinity and hydro regime. We sampled several Ruppia populations within this wetland. We used both chloroplast and nuclear microsatellite markers to identify each sample and reconstruct the local genetic structure of the two parental species and their hybrids. Afterwards, we tested whether different species had different habitat preferences. Our results confirmed that R. maritima and R. spiralis are two strongly divergent species with different reproductive ecologies and different habitat preferences. This prevents frequent hybridization and consequently we could not detect any trace of a recent hybridization event. However, we found several populations of later-generation hybrids, including a population of R. maritima x hybrid backcrosses. These hybrid populations occupy a different habitat and are genetically distinct from their parental species, although they tend to be morphological similar to parental R. maritima. Although hybridization and introgression in Ruppia is less frequent than we expected, the taxonomy of Ruppia is complicated due to ancient hybridizations and several back-crossings.